2003
DOI: 10.3141/1854-21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Underreporting on Mileage and Travel Time Estimates: Results from Global Positioning System-Enhanced Household Travel Survey

Abstract: Trip underreporting has long been a problem in household travel surveys because of the self-reporting nature of traditional survey methods. Memory decay, failure to understand or to follow survey instructions, unwillingness to report full details of travel, and simple carelessness have all contributed to the incomplete collection of travel data in self-reporting surveys. Because household trip survey data are the primary input into trip generation models, it has a potentially serious impact on transportation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(94 citation statements)
references
References 3 publications
(5 reference statements)
2
91
0
1
Order By: Relevance
“…Wolf et al (2003a;2003b) found the main causes of trip "under-reporting" to be survey length, memory decay of respondents, failure to understand or to follow survey instructions, respondents considering the trips unimportant, unwillingness to report full details of travel, and carelessness. Zmud and Wolf (2003) compared survey diary-reported trips (or simply "survey trips" from hereon) with GPS-recorded trips, and identified key demographic factors that may contribute to misreporting of trips, again assuming GPS to be the correct source of data (in the rest of this section, for ease in wording, we will assume the GPS data to be the "truth", as has been the norm in earlier studies).…”
Section: Gps In Household Travel Surveysmentioning
confidence: 99%
“…Wolf et al (2003a;2003b) found the main causes of trip "under-reporting" to be survey length, memory decay of respondents, failure to understand or to follow survey instructions, respondents considering the trips unimportant, unwillingness to report full details of travel, and carelessness. Zmud and Wolf (2003) compared survey diary-reported trips (or simply "survey trips" from hereon) with GPS-recorded trips, and identified key demographic factors that may contribute to misreporting of trips, again assuming GPS to be the correct source of data (in the rest of this section, for ease in wording, we will assume the GPS data to be the "truth", as has been the norm in earlier studies).…”
Section: Gps In Household Travel Surveysmentioning
confidence: 99%
“…Various studies confirm that the use of GPS data loggers has resulted in greater data accuracy compared to conventional paper diaries and telephone surveys (Forrest and Pearson 2005;Ohmori et al 2005;Wolf et al 2003). Accuracy is further enhanced when GPS data is used on a geographic information system (GIS) application (Chung and Shalaby 2005;Schönfelder et al 2002;Tsui and Shalaby 2006;Wolf et al 2001).…”
Section: Gps Onlymentioning
confidence: 92%
“…One of the most common methods used to gather this type of information is via travel diaries, where users declare how and why they are traveling to their destinations during a certain time period (usually of one day). The classical approaches relied on users filling up paper diaries, having phone interviews, or declaring how they traveled via web forms, which have two main downsides: the participants are under-reporting their trips (Bricka & Bhat, 2006;Wolf, Oliveira, & Thompson, 2003), and the response rate is decreasing (Ogle et al, 2005;Zimowski, Tourangeau, Ghadialy, & Pedlow, 1997). As a solution to these problems, transportation scientists tried to automate parts of these diaries.…”
Section: Transportation Sciencementioning
confidence: 99%